MASALAH â€œLEGAL STANDINGâ€ DALAM PUTUSAN - PUTUSAN HAK UJI MATERIIL MAHKAMAH AGUNG REPUBLIK INDONESIA TAHUN 2012 â€“ 2014 - Elpah, Dani (Jurnal Hukum dan Peradilan, 2015)
The paradigm has changed from disadvantaged right equalized with the interest, without classifying the requirement of disadvantaged right that must fulfill 5 (five) requirement, those are : (a) there is a right for applicant that is given on law and regulation (b) this right is disadvantaged if considered by applicant c) the disadvantage must be specific and actual orÂ at least potential (d) causality connectivity must be exist; (e) the disadvantage will not happen if the application is acceptedKeywords : Legal Standing, Judicial Review, Supreme Court